2007
DOI: 10.1063/1.2756059
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of nanoindentation of amorphous silicon carbide

Abstract: Through molecular dynamics simulation of nanoindentation of amorphous a-SiC, we have found a correlation between its atomic structure and the load-displacement ͑P-h͒ curve. We show that a density profile of a-SiC exhibits oscillations normal to the surface, analogous to liquid metal surfaces. Short-range P-h response of a-SiC is similar to that of crystalline 3C-SiC, e.g., it shows a series of load drops associated with local rearrangements of atoms. However, the load drops are less pronounced than in 3C-SiC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 98 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…1c. A molecular dynamics study showed that load drops are associated with local rearrangements of atoms (Szlufarska et al, 2007). …”
Section: Nanoindentation Of Crystalline Materialsmentioning
confidence: 99%
“…1c. A molecular dynamics study showed that load drops are associated with local rearrangements of atoms (Szlufarska et al, 2007). …”
Section: Nanoindentation Of Crystalline Materialsmentioning
confidence: 99%
“…In this new scheme, Eqs. (33) and (34) By appropriately choosing the frequency weight function Q(ω), one can simulate a GLE dynamics with a colored noise which is no longer proportional to the memory kernel.…”
Section: Appendix D: Gle Not Constrained By the Fluctuation-dissipatimentioning
confidence: 99%
“…In some instances [15,33,41], the equilibrium thermostats are applied to all atoms of the system in order to impose a specific temperature, while in other studies [7,[34][35][36][37][38][39][40], the Nosé [28], Hoover [30], or Berendsen [42] thermostats were used to thermostat only certain regions of the systems, although, strictly speaking, they were only proven to work if applied to the whole system (and additionally the Berendsen thermostat is not truly canonical). When these equilibrium thermostats are applied to nonequilibrium MD simulations, they introduce artifacts into the resulting trajectories in these simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, the chosen atoms would normally belong to several layers at the bottom of the substrate and the top of the upper sliding surface, next to the fixed layers served to mimic the missing bulk of the two surfaces. References [15,16,17,18,19,20,21] correspond to the first group, where we can see examples of velocity rescaling [17,18,19,21], Berendsen [15,20] and Nosé [16] thermostats used. The outer parts of the system (i.e.…”
Section: Introductionmentioning
confidence: 99%